Suspended over water. Medieval Marian images invoked against floods in Northern and Central Italy (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Between the Renaissance and the modern era, some medieval images attributed to Saint Luke appeared in the chronicles as the object of particoular devotional practices related to catastrophic atmospheric events. This paper four Icons of the Virgin Mary are compared, coming from different city contexts of Central and Northen Italy, dating from the 13th and the 15th Century, in order to explore their function as protectors against floods and droughts.
Keywords: Christian Iconography; Medieval Mediterranean Art; Virgin Mary; Icons; Saint Luke as Painter; Miraculous Images